The God who is beauty : beauty as a divine name in Thomas Aquinas and Dionysius the Areopagite - Sammon, Brendan Thomas (Princeton theological monograph series, 2013)
In the beginning was beauty, and beauty was with God, and beauty was God. If the tradition of divine names, that (in its Christian form) originates with Dionysius the Areopagite and includes among its ranks Albert the Great, Thomas Aquinas, and others, is correct in identifying God with the name beauty, then repurposing the Prologue to John's Gospel in this way seems hardly controversial. For if beauty is a divine name then not only is it fitting to say God is beautiful, but it is equally fitting to say that God is beauty itself. However, like most arguments from fittingness-that is to say, ar.